The intracellular functions of alpha6beta4 integrin are regulated by EGF (The Rockefeller University Press, 1996)
Upon ligand binding, the alpha6beta4 integrin becomes phosphorylated on tyrosine residues and combines sequentially with the adaptor molecules Shc and Grb2, linking to the ras pathway, and with cytoskeletal elements of hemidesmosomes. Since alpha6beta4 is expressed in a variety of tissues regulated by the EGF receptor (EGFR), we have examined the effect of EGF on the cytoskeletal and signaling functions of alpha6beta4. Experiments of immunoblotting with anti-phosphotyrosine antibodies and immunoprecipitation followed by phosphoamino acid analysis and phosphopeptide mapping showed that activation of the EGFR causes phosphorylation of the beta4 subunit at multiple tyrosine residues, and this event requires ligation of the integrin by laminins or specific antibodies. Immunoprecipitation experiments indicated that stimulation with EGF does not result in association of alpha6beta4 with Shc. In contrast, EGF can partially suppress the recruitment of Shc to ligated alpha6beta4. Immunofluorescent analysis revealed that EGF treatment does not induce increased assembly of hemidesmosomes, but instead causes a deterioration of these adhesive structures. Finally, Boyden chamber assays indicated that exposure to EGF results in upregulation of alpha6beta4-mediated cell migration toward laminins. We conclude that EGF-dependent signals suppress the association of activated alpha6beta4 with both signaling and cytoskeletal molecules, but upregulate alpha6beta4-dependent cell migration. The changes in alpha6beta4 function induced by EGF may play a role during wound healing and tumorigenesis.